metal contents in Parmelia caperata(L.) Ach. compared to bulk deposition, throughfall and leaf-wash fluxes in two holm oak forests in Montseny (NE Spain) (Atmospheric Environment, 1999)
The metal concentrations of V, Cr, Co, Ni, Cu, Zn, Cd, Hg and Pb were analysed in distilled water extracts of Parmelia caperata and in bulk deposition, throughfall and an experimental in situ washing of leaves at two forests at Montseny (NE Spain) submitted to di¤erential exposure to the industrial and tra¦c activities around Barcelona. Lichen concentra- tions of Zn, Cu, V, and Cd were higher at the site of greater exposure to pollutants. Consistently, there was higher dry deposition of these metals at the more exposed site. The order of abundance of trace metals in the lichen was similar to that in the deposition variables, although Pb and Cu had intermediate concentrations in the lichen but were very low in the deposition measurements. This indicated the higher a¦nity of Pb and Cu for the exchange sites in the lichen cell wall and the fact that lichens accumulated Pb for the last 12Ð18 y when emissions were much higher than today. The ability of Parmelia caperata to indicate the deposition of heavy metals, together with its easy sampling and handling, its broad distribution and its easy identiÞcation suggest that the lichen extract procedure described here could be used to establish gradients of atmospheric deposition of heavy metals at a general geographic level